Making Meaning of Reducing Boarding House Costs during the COVID-19 Pandemic - Dewa Made Adi Dharma; Mohammad Iqbal Bakry; Jurana Jurana (Jurnal Ilmiah Akuntansi, 2022)
This study aims to investigate the meaning of "cost" of boarding houses in the COVID-19 pandemic for boarding house entrepreneurs in Palu City, Central Sulawesi, Indonesia. This study uses the transcendental phenomenology approach of the interpretive paradigm. The interview, observation, and documentation were used to collect research data. The results of the study found three types of costs during the COVID-19 pandemic. First, the cost of boarding is interpreted as a noble good. Second, the cost of boarding is interpreted as a benefit to others. Third, the cost of boarding is interpreted as a deferred liability. These three meanings were then synergized into a sense of gratitude as a result of exploring the essence and meaning of bearing costs during the COVID-19 pandemic.